The positive role of polygamy in reducing women socio-related problems in Malaysia - Fatah Yasin, Raudlotul Firdaus; Jani, Mohd. Shah (2012)
Islam has never imposed polygamy as a universal principle nor has it put a restriction on the plurality of wives. In other words, Islam neither compels Muslims to practice polygamy nor prohibits them from doing so if certain conditions are fulfilled. Islam came at a time when people were scrambling to marry as many women as they could, just for fun and for the sake of leisure and pleasure. After a careful scrutiny of the situation, Islam regulates it and gives it a human face. It could have been prohibited like other pre-Islamic practices, such as gambling, adultery, fornication, drinking, etc. But as a way of life that takes cognisance of natural impulse of humankind, Islam arrives with its primary sources – the Qur’Én and Sunnah – to serve as unbiased umpire between a man and his wives. This paper seeks to elucidate how Islam ensures that polygamy means to protect the rights and well-being of women, by making them proud of their union with a lawful husband. In the same vein, products of such union are also regarded as bona fide offspring of the man. Islam also saves women through polygamy from illegal relationships that are detrimental to the persons involved and the society at large. To avoid being in a relationship as a mistress or concubine, who is solely responsible for single parenthood and to overcome the increasing number of divorce in some societies today, Islam ameliorates the plight of women as a result of disparity in man-to-woman ratio by offering a solution that alleviates a woman’s status from being a mere object or commodity in the hands of men. A number of Qur’anic verses and Prophetic traditions are quoted and analysed, so as to identify the objective wisdom behind the permissibility of polygamy. (Key words: polygamy, positive role, women socio-related problems)